Synthesis and Theoretical Study of Zinc(II) and Nickel(II)-Complexes of 5-Methoxyisatin 3-[N-(4-chlorophenyl)thiosemicarbazone] - Fatma Kandermirli; Murat Saracoglu; Gamze Bulut; Eno Ebenso; Taner Arslan; Asgar Kayan (Institute for Research and Community Services (LPPM) ITB, 2012)
Zinc(II) and nickel(II)-complexes of 5-methoxyisatin 3-[N-(4-chlorophenyl) thiosemicarbazone] (H2MICP) were synthesized and characterized by infrared, ultraviolet and 1H-NMR spectroscopies as well as elemental analysis. Model of H2MICP and its zinc(II) and nickel(II)-complexes were optimized with B3LYP method using 6-31G(d,p), 6-311G(d,p), 6-311++G(d,p), 6-311++G(2d,2p) basis sets. The calculated 1H-NMR, UV and IR spectra data were compared with experimental results. In addition to the Natural Bond Orbital (NBO) analysis of H2MICP and its Zinc(II) and Nickel(II) complexes, Fukui functions of H2MICP were also reported.